Evaluation of heavy and trace metals in the fish species oreochromis niloticus and alestes longipinnis from alaro Stream in Ibadan, Nigeria (2014)
An evaluation of the heavy and trace metals in the fish organs of Oreochromis niloticus and Alestes longipinnis from a tropical Alaro Stream in Ibadan, Nigeria was carried out. The aim of the study was to evaluate the concentration of heavy and trace metals in the organs of the fish species and to compare them with World Health Organization standards for human safety and exposure through consumption. Cast nets with mesh sizes ranging between 30-50mm of varying dimensional sizes were used for trapping the two fish species. Fish dissections were carried out using dissecting set to remove the gills, gut, bone, liver, fins and muscle which were oven dried at 1050C for 6hours.Pulverized tissues and organs were acid-digested for heavy and trace metal analyses using the inductively coupled plasma-mass spectrometer (ICP-MS). The results showed that the mean concentration of heavy and trace metals were comparatively higher in Oreochromis niloticus: Mn(5612.7ppm,liver) and As (0.865ppm, muscle), while Na (15278ppm, liver), Mg (10245ppm, liver), K (30128ppm, liver), Ca (247186ppm, bones), V (13.82ppm, liver), Fe (10959.3ppm, liver), Co (8.56ppm, liver), Ni (5.82ppm, liver), Cu (175.78ppm, liver), Zn (274.6ppm, liver), Se (11.80ppm, liver), Mo (1.72ppm, liver), Ag (2.33ppm, liver), Cd (2.87 ppm, bone) and Pb (14.12ppm, gills) were higher in Alestes longipinnis. As, Ag, Cd and Pb exceeded the recommended limits set by the World Health Organization for most of the fish organs in Oreochromis niloticus and Alestes longipinnis. These results show that these fish species caught from Alaro stream which is polluted by industrial pollutants are not safe for human consumption